In silico comparative analysis of the complete chloroplast genome sequences in different jewel orchid species - MINH PHUONG NGUYEN; THI HUONG TRINH; THI KIM ANH NGO; SASANTI WIDIARSIH; VIET THE HO (Nusantara Bioscience, 2023)
Abstract. Nguyen MP, Trinh TH, Ngo TKA, Widiarsih S, Ho VT. 2023. In silico comparative analysis of the complete chloroplast genome sequences in different jewel orchid species. Nusantara Bioscience 15: 12-21. Jewel orchid is the common name of several orchid species which can be alike in morphological characteristics but variable in medicinal properties. As these plants are utilized to treat several diseases, their natural existence in the wild habitat is rapidly diminished. Therefore, a better understanding of the genetic information of this plant for better genetic conservation and development of these plants is necessary. In this study, a total of 18 published chloroplast genomes of 18 jewel orchid species determined by the next-generation sequencing method were retrieved from NCBI GenBank and targeted for genomic characterization and phylogenetic analyses. Different bioinformatics tools were utilized to characterize these genomes’ genomic structure, repetitive sequences, interspecific variation, divergence, and phylogenetic relationships. The obtained data revealed that the chloroplast genomes of different jewel orchid species varied in length between 151,414 (Anoectochilus formosanus MN880624.1) and 154,375 (Goodyera biflora OM314910.1). Each species contains 34-87 SSR loci which could be useful as molecular markers for further genetic diversity study of this plant. Structural variations in the expansion and contraction of inverted repeat regions were also considered. Phylogenetic analysis identified a close relationship among species belonging to the Goodyera genus, and this genus is distinctive from other genera such as Anoectochilus, Cystorchis, Dossinia, Ludisia, and Macodes. The obtained results show a high potential of deeper characterizing the chloroplast genome of jewel orchids for species classification, identification, molecular breeding, and evolutionary exploration of these important herbal plants.